2018
DOI: 10.21597/jist.407894
|View full text |Cite
|
Sign up to set email alerts
|

Erzurum İli Narman İlçesi Sığır Yetiştiricilerinin Sığır Besleme Tercihleri

Abstract: Bu araştırma, sığır yetiştiricilerinin sığır besleme ve yemleme alışkanlıklarını ortaya koymak amacıyla Erzurum İli Narman İlçesi'nde yapılmıştır. Bu amaçla Narman ilçe ve köylerinde 208 işletme sahibiyle anket çalışması yapılarak veriler elde edilmiştir. Araştırmada elde edilen bulgulara göre yetiştiricilerin % 80.8'inin yem bitkisi üretimi yaptığı saptanmıştır. Bu işletmelerde çoğunlukla yonca (% 61.5) ve arpa (% 60.1) üretimi yapıldığı belirlenmiştir. Ancak önemli kaba yem kaynağı olan silajlık mısır üretim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 6 publications
1
8
0
Order By: Relevance
“…Results of the current study revealed that 91.5% of the enterprises in central county of Ağrı Province produced forage crops on their own fields (Figure 1a). Similarly, percentages of cattle farms produced their own forage crops in Kars Province, in Muş Province, Narman county, in Tekirdağ and Kırklareli provinces were reported as 87.8%, 80.8%, 88.7%, 91.6% and 81.8% respectively by Demir et al, (2013), Bakır and Kibar, (2018), Diler et al, (2018) and Öztürk et al, (2019). On the contrary of results of the present study, findings of other studies conducted in Turkey revealed lower percentages of enterprises produced their own forage crops in Konya (47.2%) as well as and in Ergani (9.0%), in Yalova (61.2%), in Erzurum (16%) (Uzal and Uğurlu 2006;Bakır and Han 2009;Demir andHan, 2014 andDiler et al 2016).…”
Section: Forage Crop Productionmentioning
confidence: 89%
“…Results of the current study revealed that 91.5% of the enterprises in central county of Ağrı Province produced forage crops on their own fields (Figure 1a). Similarly, percentages of cattle farms produced their own forage crops in Kars Province, in Muş Province, Narman county, in Tekirdağ and Kırklareli provinces were reported as 87.8%, 80.8%, 88.7%, 91.6% and 81.8% respectively by Demir et al, (2013), Bakır and Kibar, (2018), Diler et al, (2018) and Öztürk et al, (2019). On the contrary of results of the present study, findings of other studies conducted in Turkey revealed lower percentages of enterprises produced their own forage crops in Konya (47.2%) as well as and in Ergani (9.0%), in Yalova (61.2%), in Erzurum (16%) (Uzal and Uğurlu 2006;Bakır and Han 2009;Demir andHan, 2014 andDiler et al 2016).…”
Section: Forage Crop Productionmentioning
confidence: 89%
“…It was also determined that alfalfa was in the first place among the most widely cultivated forage crops. Similarly, Diler et al (2018), Bakır and Kibar (2019) and Sezer et al (2020) reported that the highest percentage of the forage crops produced in the cattle enterprises in Narman county of Erzurum province, in Muş province and in Nevşehir province belonged to alfalfa. On the other hand, commonly produced forage crops in Tekirdağ and Kırklareli provinces were noted as corn for silage and alfalfa by Öztürk et al (2019).…”
Section: Cultivation Of Fodder Cropsmentioning
confidence: 92%
“…In central county of Erzincan province, 74.8% of owners of the enterprises sowed forage crops on their own farms, while 25.2% of those do not produce forage crops in their enterprises. Similarly, more than 3/4 of the cattle enterprises in Antalya, Iğdır, Kars, Muş, Tekirdağ, Kırklareli provinces as well as Narman county of Erzurum province grew fodder crops, that they needed, on their own farms (Kum, 2006;Yeşil, 2015;Demir et al, 2013;Bakır and Kibar, 2019;Öztürk et al, 2019;Diler et al, 2018). On the contrary of results of the present study, findings of other studies carried out in different regions of Turkey revealed lower percentages (47.2% in Konya 52.0 in Tekirdağ, 61.2% in Yalova, 16% in Hınıs county of Erzurum province) of enterprises which grew their own forage crops (Uzal and Uğurlu 2006;Soyak et al 2007;Bakır and Han, 2014;Diler et al 2016).…”
Section: Sources Of Roughage and Concentrate Feed Supplymentioning
confidence: 99%
See 2 more Smart Citations